Analysing tactical knowledge through team sport assessment procedure / TSAP: a case study in basketball - Catarino, L. M.; Carvalho, H. M.; Gonçalves, C. E. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
During the season players can be observed and evaluated in two environments: game context and training context. In basketball, the absence of a valid and reliable instrument to use in order to assess objectively the level of tactical awareness is a main problem in training processes and coaching communities. Team Sport Assessment Procedure was devised by Grehaigne, Godbout & Bouthier providing teachers with objective data on students’ offensive performance. Two professional players were observed through video analysis by three observers in order to ascertain the validity of TSAP in basketball’s tactical observation in game context. Cohen’s k coefficient value (k=0.88) reveals an almost perfect inter-observer agreement meaning that observers registered the same actions and interpreted them in the same way. The results shown that TSAP is a valid and reliable tool to assess the offensive on-ball elements of the game and easy to be used by coaches and athletes.